Changes in perceived job satisfaction during the transition from adolescence to young adulthood - Śliwicki, Dominik; Osińska, Magdalena; Szczepaniak, Małgorzata; Szulc-Obłoza, Agnieszka (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: This study aims to identify and compare the determinants of perceived overall job satisfaction among post-adolescents (aged 18-24) and young adults (aged 25-29) in Poland. Methodology: In considering the differences in the early adulthood life phases corresponding with financial independence, education level, and professional experience, the author concentrated on post-adolescence as the phase of life before young adulthood. Using data from a survey of 800 respondents, divided equally between the two age groups in Poland, ordered logit models were estimated and a scenario analysis derived. Results: The results revealed that perceived job satisfaction was higher in the group of young adults. Economic factors, particularly salary and consumption satisfaction, had a significantly greater impact on post-adolescents. The scenario analysis indicated that improvements in these factors could yield substantial gains in perceived job satisfaction, especially for the younger group. Implications and recommendations: The functioning of the labour market, especially of youth and young adults, is associated with challenges for employers at microeconomic level and with employment policy at macroeconomic level. For these reasons it was justified to create a system for monitoring the broadly understood satisfaction with various aspects of life and professional activity that consider life-cycle stages and generational differences. Monitoring satisfaction will allow employers to respond to changing moods, especially regarding young employees. Originality/value: This study updates and contextualises the literature on job satisfaction by incorporating a life-cycle perspective and comparing two adjacent generational cohorts (early Gen Z and late Gen Y). Answers to the research questions regarding: the relationship between age and job satisfaction, the difference between the factors shaping job satisfaction in both groups, and the strategies that could help increase job satisfaction among young people fill the gap between the well-established recognition of job satisfaction factors made in the 1990s, and the current trends. Keywords: job satisfaction, young adults, ordered logit model, scenario analysis
Argumenta Oeconomica, 2025, Nr 2 (55), s. 1-20
Keywords: job satisfaction; young adults; ordered logit model; scenario analysis